Pelatihan Peramalan Permintaan Berbasis Machine Learning untuk Optimalisasi Produksi Mendukung SDG 8 - Riyadi, Selamet; Kholil, Muhammad; Rukyat, Nanang; Pranoto, Hadi; Haekal, Jakfat (IRA Jurnal Pengabdian Kepada Masyarakat (IRAJPKM), 2025)
This community service program aims to enhance the capabilities of business actors and industry practitioners to apply machine learning-based demand forecasting to optimize production and support the achievement of SDG 8. The training was conducted through interactive workshops consisting of conceptual introduction, hands-on model development, and analysis of forecasting results using production datasets. Participants were guided in variable selection, model accuracy evaluation, and the use of prediction outputs for production decision-making. Evaluation results indicate an 85% improvement in participants' understanding of forecasting concepts and an 80% increase in software-use competence. This program contributes to improving technological literacy, enhancing production planning efficiency, and building digital capacity as part of sustainable economic development.